Changes in Insulin-like Growth Factor-1 Level in Patients with Sepsis and Septic Shock - Sang Hoon Lee; Byung Hoon Park; Joo Han Song; Song Yee Kim; Kyung Soo Chung; Eun Young Kim; Ji Ye Jung; Young Sam Kim; Se Kyu Kim; Joon Chang; Moo Suk Park (Korean Journal of Critical Care Medicine, 2016)
Background Despite many ongoing, prospective studies on the topic, sepsis still remains one of the main causes of death in hospital. The hormone insulin-like growth factor 1 (IGF-1) has a similar molecular structure to that of insulin. IGF-1 exerts anabolic effects and plays important roles in both normal physiology and pathologic processes. Previous studies have observed low serum IGF-1 level in patients with critical illnesses. Here, we evaluated changes in IGF-1 level based on survival of septic patients. Methods We evaluated 140 patients with sepsis and septic shock (21 with sepsis and 119 with septic shock) admitted to the intensive care unit of a university-affiliated hospital in Korea. Serum IGF-1 level was measured on days 0, 1, 3, and 7. Patients with liver disease were excluded from this study. All data were analyzed using SPSS version 20 (SPSS Inc., Chicago, IL, USA). Results Patients with septic shock had significantly lower serum IGF-1 level on days 1 and 3 than patients without septic shock (p = 0.002 and p = 0.007, respectively). Generally, there was a negative relationship between IGF-1 and serum cortisol levels; however, this relationship was only significant on day 3 (p = 0.029). Furthermore, renin showed significantly negative correlation with IGF-1 on day 3 (p = 0.038). IGF-1 level did not show significant difference between survivors and non-survivors. Conclusions Our results showed that IGF-1 was associated with septic shock, and that the IGF-1 axis is severely disrupted in septic patients. Additionally, serum cortisol and renin levels were associated with IGF-1 level.